How Stripe invests in technical infrastructure (O'Reilly Media, 2019)
"Will Larson (Stripe) unpacks the process of picking and prioritizing technical infrastructure work, which is rarely if ever discussed but is so essential to long-term company success. Will shares Stripe's approach to evolving your approach to prioritizing infrastructure as your company scales, justifying, and maybe even expanding, your company's spend on technical infrastructure, exploring the whole range of possible areas to invest into infrastructure, adapting your approach between periods of firefighting and periods of innovation, and balancing investment in supporting existing products and enabling new product development. You'll come away with a broad set of tools, frameworks, and ideas for plotting the future of your technical infrastructure. This session was recorded at the 2019 O'Reilly Velocity Conference in San Jose."--Resource description page